Identifikasi Senyawa Metabolit Sekunder Daun Spigelia anthelmia L. dan Uji Aktifitas Antioksidan Menggunakan Metode DPPH (1,1-Diphenyl-2-Picrylhidrazy) - Muhammad Taupik; A. Mu’thi Andy Suryadi; Samsul Bahri Badjeber; Wiwit Zuriati Uno; Jafar La Kilo (Journal Syifa Sciences and Clinical Research, 2022)
Spigelia anthelmia is a type of weed plant that is classified as toxic and is included in the list of herb of medicine. The research aims to determine the secondary metabolite content of Spigelia anthelmia L. leaves extract and antioxidant activity test using the DPPH (1,1-Diphenyl-2-Picrylhydrazy) method. The research samples are extracted by applying the total maceration method with methanol as a solvent and followed by partition method using n-hexane, ethyl acetate, and methanol as solvents. The identification of flavonoid compounds content is performed by employing Thin Layer Chromatography method with methanol as eluent: n-hexane (1:4), ethyl acetate:n-hexane (4:1), ethyl acetate:n-hexane (4:1). Meanwhile, the antioxidant activity test is performed by employing UV-Vis Spectrophotometry method. The result of identification by thin layer chromatography using AlCl3 spray reagent, Lieberman Burchard. Dragendrof, and cerium sulfate, indicate that the Spigelia anthelmia L. leaves extract contains alkaloids, flavonoids, and terpenoids. In addition, the antioxidant activity test of Spigelia anthelmia L. leaves extract is carried out at wavelength of UV 516 nm with an absorbance value of 0,654 A. with a linear equation of y = 0,027 x – 42,83 with a correlation coefficient (R2) = 0,0983 and has the strongest IC50 at the methanol fraction for 7,69 µg/ml.